MERLIN: a novel BRET-based proximity biosensor for studying mitochondria-ER contact sites - Hertlein, Vanessa; Fischer, Sebastian (Life science alliance, 2020)
The contacts between the ER and mitochondria play a key role in cellular functions such as the exchange of lipids and calcium between both organelles, as well as in apoptosis and autophagy signaling. The molecular architecture and spatiotemporal regulation of these distinct contact regions remain obscure and there is a need for new tools that enable tackling these questions. Here, we present a new bioluminescence resonance energy transfer-based biosensor for the quantitative analysis of distances between the ER and mitochondria that we call MERLIN (Mitochondria-ER Length Indicator Nanosensor). The main advantages of MERLIN compared with available alternatives are that it does not rely on the formation of artificial physical links between the two organelles, which could lead to artifacts, and that it allows to study contact site reversibility and dynamics. We show the applicability of MERLIN by characterizing the role of the mitochondrial dynamics machinery on the contacts of this organelle with the ER.
Published online: 9 December 2019
Gesehen am 10.03.2020